The influence of residual salivary fluoride from dentifrice on enamel erosion: An in situ study - Magalhães, Ana Carolina [UNESP]; Rios, Daniela; Martinhon, Cleide Cristina Rodrigues [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Buzalof, Marilia Afonso Rabelo; Machado, Maria Aparecida de Andrade Moreira (FapUNIFESP (SciELO), 2008)
The objective of this study was to assess the salivary residual effect of fluoride dentifrice on human enamel subjected to an erosive challenge. This crossover in situ study was performed in two phases (A and B), involving ten volunteers. In each phase, they wore acrylic palatal appliances, each containing 3 human enamel blocks, during 7 days. The blocks were subjected to erosion by immersion of the appliances in a cola drink for 5 minutes, 4 times a day. Dentifrice was used to brush the volunteers' teeth, 4 times a day, during 1 minute, before the appliance was replaced into the mouth. In phases A and B the dentifrices used had the same formulation, except for the absence (PD) or presence (FD) of fluoride, respectively. Enamel alterations were determined using profilometry, microhardness (%SMHC), acid- and alkali-soluble F analysis. The data were tested using ANOVA (p < 0.05). The concentrations (mean ± SD) of alkali- and acid-soluble F (μgF/cm 2) were, respectively, PD: 1.27 a ± 0.70/2.24∧ A ± 0.36 and FD: 1.49 a ± 0.44/2.24∧ ± 0.67 (p > 0.05). The mean wear values (± SD, μm) were PD: 3.63 a ± 1.54 and FD: 3.54 a ± 0.90 (p > 0.05). The mean %SMHC values (± SD) were PD: 89.63 a ± 4.73 and FD: 87.28 a ± 4.01 (p > 0.05). Thus, we concluded that the residual fluoride from the fluoride-containing dentifrice did not protect enamel against erosion.
Keywords: Dental enamel; Fluorine; Tooth erosion; anticaries agent; fluoride varnish; toothpaste; analysis of variance; carbonated beverage; chemically induced disorder; clinical trial; controlled clinical trial; crossover procedure; double blind procedure; randomized controlled trial; tooth disease; Cariostatic Agents; Dentifrices; Double-Blind Method; Fluorides, Topical; Tooth Abrasion; Tooth Erosion